Alternative history attack success probability calculation in blockchain system - Safonenko, Vladyslav; Goncharov, Nikita; Datsenko, Sergey; Poluyanenko, Nikolay; Lazareva, Elizaveta (Computer Science and Cybersecurity, 2019)
This article systemizes the information on the subject of the alternative history attack of the blockchain registry. The review and generalization of the information presented in the most respected works in this direction is offered. The analysis of corresponding works on estimation of probability of double spending in the "Proof of Work" consensus protocol is carried out. The problems of the player's ruin are considered and an analogy with the attack of double spending on the blockchain is made. Poisson's experiment for the general case is considered. The models on the basis of which S. Nakamoto and M. Rosenfeld made attempts to get a quantitative estimation of probability of successful double spending attack on some algorithms of consensus having probability completeness are analyzed. Simplifications and assumptions that take place in the respective models with the help of which the final expression is obtained are given.